Integration Questions

Question Number 123998 by john_santu last updated on 30/Nov/20

$$\:\int_{\:\mathrm{0}} ^{\:\infty} \:\frac{{x}^{\mathrm{2}} }{\left(\mathrm{1}+{x}^{\mathrm{2}} \right)^{\mathrm{2}} }\:{dx}\: \\$$

Answered by liberty last updated on 30/Nov/20

$$\:{substituting}\:{x}\:=\:\mathrm{tan}\:{q}\:{with}\:{upper}\:{limit}\:\frac{\pi}{\mathrm{2}} \\$$$${and}\:{lower}\:{limit}\:\mathrm{0} \\$$$$\int_{\:\mathrm{0}} ^{\:\pi/\mathrm{2}} \:\frac{\mathrm{tan}\:^{\mathrm{2}} {q}\:.\mathrm{sec}\:^{\mathrm{2}} {q}\:{dq}}{\mathrm{sec}\:^{\mathrm{4}} {q}}\:=\:\int_{\:\mathrm{0}\:} ^{\:\pi/\mathrm{2}} \mathrm{sin}\:^{\mathrm{2}} {q}\:{dq}\: \\$$$$\:=\:\int_{\:\mathrm{0}} ^{\:\pi/\mathrm{2}} \left(\frac{\mathrm{1}}{\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\:\mathrm{2}{q}\:\right){dq}\:=\:\left[\frac{\mathrm{1}}{\mathrm{2}}{q}−\frac{\mathrm{1}}{\mathrm{4}}\mathrm{sin}\:\mathrm{2}{q}\:\right]_{\:\mathrm{0}} ^{\pi/\mathrm{2}} \\$$$$\:=\:\frac{\pi}{\mathrm{4}}. \\$$

Answered by Dwaipayan Shikari last updated on 30/Nov/20

$$\int_{\mathrm{0}} ^{\infty} \frac{{x}^{\mathrm{2}} }{\left(\mathrm{1}+{x}^{\mathrm{2}} \right)^{\mathrm{2}} }{dx}\:\:\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{1}+{x}^{\mathrm{2}} }={t}\Rightarrow−\frac{\mathrm{2}{x}}{\left(\mathrm{1}+{x}^{\mathrm{2}} \right)^{\mathrm{2}} }=\frac{{dt}}{{dx}}\:\:\:\:\:\:{x}=\sqrt{\frac{\mathrm{1}−{t}}{{t}}} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\mathrm{1}} \sqrt{\frac{\mathrm{1}−{t}}{{t}}}\:{dt}\:\:=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\mathrm{1}} {t}^{−\frac{\mathrm{1}}{\mathrm{2}}} \left(\mathrm{1}−{t}\right)^{\frac{\mathrm{1}}{\mathrm{2}}} {dt}=\frac{\mathrm{1}}{\mathrm{2}}\beta\left(\frac{\mathrm{1}}{\mathrm{2}},\frac{\mathrm{3}}{\mathrm{2}}\right) \\$$$$=\frac{\Gamma^{\mathrm{2}} \left(\frac{\mathrm{1}}{\mathrm{2}}\right)}{\mathrm{4}}=\frac{\sqrt{\pi}.\sqrt{\pi}}{\mathrm{4}}=\frac{\pi}{\mathrm{4}} \\$$

Answered by mathmax by abdo last updated on 30/Nov/20

$$\mathrm{I}=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{x}^{\mathrm{2}} }{\left(\mathrm{x}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\mathrm{dx}\:\Rightarrow\mathrm{I}\:=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{x}^{\mathrm{2}} +\mathrm{1}−\mathrm{1}}{\left(\mathrm{x}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\mathrm{dx} \\$$$$=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{dx}}{\mathrm{x}^{\mathrm{2}} \:+\mathrm{1}}−\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{dx}}{\left(\mathrm{x}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{2}} }=\frac{\pi}{\mathrm{2}}−\mathrm{J}\:\mathrm{with}\:\mathrm{J}=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{dx}}{\left(\mathrm{x}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{2}} } \\$$$$\mathrm{2J}=\int_{−\infty} ^{+\infty} \:\frac{\mathrm{dx}}{\left(\mathrm{x}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{2}} }\:\mathrm{let}\:\varphi\left(\mathrm{z}\right)=\frac{\mathrm{1}}{\left(\mathrm{z}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{2}} }\:=\frac{\mathrm{1}}{\left(\mathrm{z}−\mathrm{i}\right)^{\mathrm{2}} \left(\mathrm{z}+\mathrm{i}\right)^{\mathrm{2}} } \\$$$$\left.\int_{−\infty} ^{+\infty} \:\varphi−\mathrm{z}\right)\mathrm{dz}\:=\mathrm{2i}\pi\:\mathrm{Res}\left(\varphi,\mathrm{i}\right) \\$$$$\mathrm{Res}\left(\varphi,\mathrm{i}\right)=\mathrm{lim}_{\mathrm{z}\rightarrow\mathrm{i}} \:\:\frac{\mathrm{1}}{\left(\mathrm{2}−\mathrm{1}\right)!}\left\{\left(\mathrm{z}−\mathrm{i}\right)^{\mathrm{2}} \varphi\left(\mathrm{z}\right)\right\}^{\left(\mathrm{1}\right)} \\$$$$=\mathrm{lim}_{\mathrm{z}\rightarrow\mathrm{i}} \:\:\:\left\{\left(\mathrm{z}+\mathrm{i}\right)^{−\mathrm{2}} \right\}^{\left(\mathrm{1}\right)} \:=\mathrm{lim}_{\mathrm{z}\rightarrow\mathrm{i}} \:\:\:−\mathrm{2}\left(\mathrm{z}+\mathrm{i}\right)^{−\mathrm{3}} \:=\mathrm{lim}_{\mathrm{z}\rightarrow\mathrm{i}} \frac{−\mathrm{2}}{\left(\mathrm{z}+\mathrm{i}\right)^{\mathrm{3}} } \\$$$$=\frac{−\mathrm{2}}{\left(\mathrm{2i}\right)^{\mathrm{3}} }\:=\frac{−\mathrm{2}}{−\mathrm{8i}}\:=\frac{\mathrm{1}}{\mathrm{4i}}\:\Rightarrow\int_{−\infty} ^{+\infty} \:\varphi\left(\mathrm{z}\right)\mathrm{dz}\:=\mathrm{2i}\pi×\frac{\mathrm{1}}{\mathrm{4i}}=\frac{\pi}{\mathrm{2}}=\mathrm{2J}\:\Rightarrow \\$$$$\mathrm{J}=\frac{\pi}{\mathrm{4}}\:\Rightarrow\:\mathrm{I}\:=\frac{\pi}{\mathrm{2}}−\frac{\pi}{\mathrm{4}}=\frac{\pi}{\mathrm{4}} \\$$

Answered by mnjuly1970 last updated on 01/Dec/20

$$\\$$$$\int_{\mathrm{0}} ^{\:\infty} \frac{\mathrm{1}+{x}^{\mathrm{2}} −\mathrm{1}}{\left(\mathrm{1}+{x}^{\mathrm{2}} \right)^{\mathrm{2}} }{dx}=\frac{\pi}{\mathrm{2}}−\frac{\pi}{\mathrm{4}}=\frac{\pi}{\mathrm{4}} \\$$